Coffee and Potato Agroecosystems: Social Construction of Spaces as a Concept to Analyse Nature's Contributions to People - Bravo-Monroy, Liliana (Frontiers in Ecology and Evolution, 2021)
Achieving goals for conservation and sustainability using nature, decision-making, and policy planning requires accurate modes of description to understand the relationship between society and the environment. Despite most planning strategies being constrained by policy objectives, planning is expected to be more participatory and inclusive of the plurality of values and all types of socio-spatial relationships. Based on Lefebvre's social theory, the objectives of this work are to propose a triad of spaces as a helpful framework to analyse nature's contributions to people (NCP), describe different spaces socially constructed by coffee and potato farmer communities in Colombia, and explore the implications for various kinds of decision-making. Using qualitative research methods, this manuscript describes three spaces: lived spaces as intangible spaces based on local, religious, and ceremonial values of NCP; perceived spaces include farmer spatial organization according to the ties of kinship and the downward course of streams, the incidence of negative NCP, such as plant diseases, and types of management crops; and conceived spaces as the overlapping of different spatial views of territorial planning. Given that NCP has great potential to integrate diversity of values about nature and cultural contexts into decision-making, the triad of social spaces offers a spatial dimension to the analyses of NCP. Lived spaces make non-material NCP and non-instrumental values more visible. Perceived spaces highlight material NCP and regulating NCP with the view that maintenance of NCP in the future is essential for relational and instrumental values, e.g., how material NCP and regulating NCP of landscapes are perceived and by whom. Conceived spaces emphasize the predominance of the intrinsic biophysical values of NCP. Thus, the triad of social spaces as a conceptual framework can be useful in the operationalization of NCP in environmental management, the governance of schemes, and the implementation of land-use plans at the local scale. By thinking of these spaces relationally, such insight can inform and enhance decisions and policymaking about the value of places toward the priorities of meeting management. The results of the study emphasize the important policy implications of recognizing lived and perceived spaces in decision-making and highlight the role of NCP in facilitating the communication of these spaces to support spatial management of land use.